TO STUDY THE PRESENCE OF RISK FACTORS FOR THE DEVELOPMENT OF ACUTE CORONARY SYNDROME IN PATIENTS OF WORKING AGE HOSPITALIZED IN EMERGENCY MEDICAL CARE (World Bulletin of Public Health, 2024)
To study the presence of risk factors for the development of acute coronary syndrome in young patients in specialized cardiology centers
Keywords: syndrome; factors; coronary; young